2009
DOI: 10.1021/ie801758e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Uniformly Sized Chitosan Nanospheres by a Premix Membrane Emulsification Technique

Abstract: Chitosan nanospheres have great potential in drug controlled release systems, because they show excellent degradability, biocompatibility, and nontoxicity. The particle size control and size distribution of nanospheres are necessary in order to improve reproducibility, bioavailability, and repeatable release behavior. In order to prepare uniformly sized and size-controllable chitosan nanospheres, in this study, a premix membrane emulsification technique was developed on the basis of direct membrane emulsificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Considering the simplicity of operation, 3 times trans-membrane passes were employed in the next preparation process. The result is in accordance with the results of the other research [23,24].…”
Section: Effect Of Number Of Trans-membrane Passes On Uniformity Of Msupporting
confidence: 92%
See 3 more Smart Citations
“…Considering the simplicity of operation, 3 times trans-membrane passes were employed in the next preparation process. The result is in accordance with the results of the other research [23,24].…”
Section: Effect Of Number Of Trans-membrane Passes On Uniformity Of Msupporting
confidence: 92%
“…Therefore, 250 kPa was used in the following study when using 5.2 μm. The optimized trans-membrane pressures for membrane pores of 2.8 μm and 1.4 μm were 300 kpa and 950 kpa respectively [23,24]. These results showed that membrane pore size will have great effect on the trans-membrane pressure, that is, the optimal trans-membrane pressure will decrease with the increase of membrane pore size.…”
Section: Effect Of Trans-membrane Pressure On Uniformity Of Microspheresmentioning
confidence: 85%
See 2 more Smart Citations
“…Particulate systems such as spheres, beads, capsules have been prepared in a micron range (Vladisavljevi c and Williams, 2005) by using membrane emulsification (ME) technology, whereas few works are reported for the preparation of particles in submicron range Lv et al, 2009;Wei et al, 2008;Sheibat-Othman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%